2014
DOI: 10.1596/1813-9450-7138
|View full text |Cite
|
Sign up to set email alerts
|

Wage Growth, Landholding, and Mechanization in Chinese Agriculture

Abstract: Summary. -This paper aims to examine the dynamics of land transactions, machine investments, and the demand for machine services using farm panel data from China. Recently, China's agriculture has experienced a large expansion of machine rentals and machine services provided by specialized agents, which has contributed to mechanization of agricultural production. On the other hand, the empirical results show that an increase in non-agricultural wage rates leads to expansion of self-cultivated land size. A rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Thus, the massive creation of nonfarm jobs to absorb rural population by offering lucrative wages is necessary to realise significant farm size expansion. The importance of non-agricultural wages to attract rural labour to nonfarm sectors can be clearly seen in the case of China (Wang et al, 2014), as shown in Figure 6. In 2000 the relationship between non-agricultural wage and migration rate (that is, the ratio of the number of migrants to the number of working age rural workers) is not so clear, except for high-wage areas.…”
Section: Migration and Farm Size Expansionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, the massive creation of nonfarm jobs to absorb rural population by offering lucrative wages is necessary to realise significant farm size expansion. The importance of non-agricultural wages to attract rural labour to nonfarm sectors can be clearly seen in the case of China (Wang et al, 2014), as shown in Figure 6. In 2000 the relationship between non-agricultural wage and migration rate (that is, the ratio of the number of migrants to the number of working age rural workers) is not so clear, except for high-wage areas.…”
Section: Migration and Farm Size Expansionmentioning
confidence: 98%
“…Moreover, it is interesting to observe large variations in real wage growth across major regions (Table 4). Yamauchi (2014) examines the dynamically changing patterns of land use, capital investments and real wages by using farm panel data from seven provinces collected in 2007 and 2010. The regression analysis shows that an increase in real wages has induced the substitution of labour by machines, notably among relatively large farmers.…”
Section: Emerging Advantage Of Large Farms In Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…CLP, like their migrant counterparts in urban areas, are able to return from school each day to their parents. However, although each rural household in China has access to cultivated land (both through contracts with the village and through rental agreements), the average operational size of a farm is only 0.6 hectares (NBSC 2014;Wang et al 2016). Hence, given the nature of China's small-scale farming sector, when husband and wife both live at home (or one spouse lives at home and the other migrates), family income can be significantly lower than when both parents migrate to cities.…”
mentioning
confidence: 99%
“…While the optimal farm size will depend on various elements including topography and production mix, some farm consolidation may improve the scope for mechanisation and vertical integration of production. With significant increases in farm wages over recent years, the incentives for substituting capital for labour have risen (Wang et al, 2014a). Some of the benefits of consolidation have been captured through strong growth in farmer professional cooperatives and equipment rental services in China.…”
mentioning
confidence: 99%